Phenological sensitivity to climate across taxa and trophic levels - Thackeray, Stephen J.; Henrys, Peter A.; Hemming, Deborah; Bell, James R.; Botham, Marc S.; Burthe, Sarah; Helaouet, Pierre; Johns, David G.; Jones, Ian D.; Leech, David I.; Mackay, Eleanor B.; Massimino, Dario; et al. (Nature (London), 2016)
Differences in phenological responses to climate change among species can desynchronise ecological interactions and thereby threaten ecosystem function. To assess these threats, we must quantify the relative impact of climate change on species at different trophic levels. Here, we apply a Climate Sensitivity Profile approach to 10,003 terrestrial and aquatic phenological data sets, spatially matched to temperature and precipitation data, to quantify variation in climate sensitivity. The direction, magnitude and timing of climate sensitivity varied markedly among organisms within taxonomic and trophic groups. Despite this variability, we detected systematic variation in the direction and magnitude of phenological climate sensitivity. Secondary consumers showed consistently lower climate sensitivity than other groups. We used mid-century climate change projections to estimate that the timing of phenological events could change more for primary consumers than for species in other trophic levels (6.2 versus 2.5–2.9 days earlier on average), with substantial taxonomic variation (1.1–14.8 days earlier on average). An ambitious study has used more than 10,000 datasets to examine how the phenological characteristics—such as the timing of reproduction—of various taxa alter in response to climate change, and suggests that differing levels of climate sensitivity could lead to the desynchronization of seasonal events over time. The shifting biological seasons Variations in the phenological responses of different species to climate change have fuelled concerns that key species interactions may desynchronize over time, with consequences for ecosystem functioning. Stephen Thackeray et al . examine the climate sensitivity of 812 terrestrial and aquatic taxa across the United Kingdom, using more than 10,000 phenological data sets spanning 1960 to 2012, together with temperature and precipitation data. There was a systematic difference in the magnitude and direction of phenological climate sensitivity across trophic levels, despite marked heterogeneity among organisms sharing taxonomic affinities and trophic position. In particular, secondary consumers showed lower levels of climate sensitivity than primary producers and consumers. The authors suggest that the differential sensitivity of phenology to climate across trophic levels could result in the desynchronization of seasonal events in the future.